Differential expansion of T peripheral helper cells in early rheumatoid arthritis and osteoarthritis synovium. Issue 2 (21st October 2022) - Murray-Brown, William; Guo, Yanxia; Small, Annabelle; Lowe, Katie; Weedon, Helen; Smith, Malcolm D; Lester, Susan E; Proudman, Susanna M; Rao, Navin L; Hao, Ling-Yang; Nagpal, Sunil; Wechalekar, Mihir D
Abstract : Objectives: Programmed cell death protein 1 (PD-1)-expressing T cells are implicated in the pathogenesis of autoimmune inflammatory diseases such as rheumatoid arthritis. A subset of CXCR5 − T cells, termed T peripheral helper (Tph) cells, which drive B cell differentiation, have been identified in ectopic lymphoid structures in established rheumatoid arthritis synovial tissue. Here, we aimed to characterise these in treatment-naïve, early rheumatoid arthritis to determine whether these cells accumulate prior to fully established disease. Methods: Fresh dissociated tissue and peripheral blood mononuclear cell (PBMC) suspensions were stained with Zombie UV, followed by anti-CD45RO, PD-1, CD3, ICOS, CD8, CD4, CD20, CXCR5, TIGIT and CD38 antibodies prior to analysis. For histology, rheumatoid arthritis synovial sections were prepared for Opal multispectral immunofluorescence with anti-CD45RO, CD20, PD-1 and CXCR5 antibodies. Images were acquired on the Perkin Elmer Vectra V.3.0 imaging system and analysed using InForm Advanced Image Analysis software. Results: Flow cytometry revealed T cell infiltration in the rheumatoid arthritis synovium with differential expression of PD-1, CD45RO, ICOS, TIGIT and CD38. We observed a higher frequency of PD1 hi CXCR5 − Tph in rheumatoid arthritis synovial tissue and PBMCs versus controls, and no significant difference in T follicular helper cell frequency. Microscopy identified a 10-fold increase of Tph cells in early rheumatoid arthritis synovial follicular and diffuse regions, and identified Tph adjacent to germinal centre B cells. Conclusions: These data demonstrate that PD-1 hi Tph cells are present in early rheumatoid arthritis, but not osteoarthritis synovium, and therefore may provide a target for treatment of patients with early rheumatoid arthritis.